Nonodontogenic Cervical Necrotizing Fasciitis Caused by Sialadenitis - Alper Yenigun; Bayram Veyseller; Omer Vural; Orhan Ozturan (Case Reports in Otolaryngology)
Necrotizing fasciitis is a rapidly progressive infectious disease of the soft tissue with high mortality and morbidity rates. Necrotizing fasciitis is occasionally located in the head and neck region and develops after odontogenic infections. Factors affecting treatment success rates are early diagnosis, appropriate antibiotic treatment, and surgical debridement. We present a necrotizing fasciitis case located in the neck region that developed after sialoadenitis. It is important to emphasize that necrotizing fasciitis to be seen in the neck region is very rare. Nonodontogenic necrotizing fasciitis is even more rare.